Inhibitory activity of Coprinopsis atramentaria extract, organic acids and their possible methylated synthesized metabolites on growth of human tumor cell lines - Heleno, Sandrina A. (2014)
Coprinopsis atramentaria (Bull.: Fr.) Redhead. Vilgalys & Moncalvo, is a wild edible mushroom previously characterized by our research group for its nutritional composition, and showed a notable antioxidant activity. p-Hydroxybenzoic (4. 71 mg/1 00 g dry weight), p coumaric (0.82 mg/ 100 g) and cinnamic (1.70 mg/100 g) acids were identified in its extract, but have been reported as common compounds in other mushrooms. In the present work, the inhibitory activity of the growth of human tumor cell lines MCF-7 (breast adenocarcinoma), NCl-H460 (non-small cell lung carcinoma), HCT 15 (colon carcinoma). 1-lcLa (cervical carcinoma) and l-l epG2 (hepatocellular carcinoma) and non-tumor porcine liver primary cell culture (PLP2). was evaluated by the sulforhodamine B assay', using C. atramentaria methanolic extract, the identified organic acids separately and their synthesized methylated possible metabolites, for MCF7, NCI-H460 and HCT 15 cell lines the extract presented high growth inhibitory activity with GI 50 values 53 .1 0±4.72. 15.13±1.35 and 36.44±3.30 pg/mL, respectively, and no activity on non tumor cells (GI 400 pg/mL). In most of the cases, methylated possible metabolites showed higher activity than the corresponding parental compounds. The substitution of the carboxylic group (in parental organic ac ids) for an ester increased the growth inhibitory activity of tumor cell lines not revealing any toxicity for non-tumor cells PLP2. Organic acids, mainly phenolic compounds, arc extensively metabolized in humans, being methylation one of the conjugated forms occurring in the organism and giving methylated metabolites. Therefore the present study contributes to understand the bioactivity of organic acids and derivative compounds. including human possible metabolites.